Discrimination of diesel by gas chromatography - Muhamad Sufiyan, Azah (Universiti Sains Malaysia, 2009)
Diesel samples from 27 service stations in Kota Bharu were collected over a period of a week were subject to GC-MS analysis. Using extracted ion chromatograms, peak area of 41 selected peaks at various mass per charge were integrated. These peak areas were then selfnormalised to ion 220b prior to Principal Component Analysis (PCA). The results show that principal component analysis is able to group the samples into a few clusters. Using the distance between replicates, however, some samples are tightly group indicating that these samples are relatively similar based on the data treatment and statistical analysis used in this study. A blind test matched the target sample indicating that the data treatment is reliable. The reliability of this approach is further supported by the close proximity between duplicates. Four samples collected from a selected service station over a period of four weeks were spread out by PCA indicating that these diesel profiles change over time. This is true if the service station received new batches of diesel after each collection of the samples.